Dynamic lipid-protein stoichiometry on E1 and E2 conformations of the Na+/K+-ATPase - Mangialavori, Irene Cecilia (2011)
Highlights: Intramembrane segments of Na+/K+-ATPase were labeled with [125I]TID-PC/16. E1-E2 transition is accompanied by changes in the number of annular lipids.